Oral ingestion of Shiikuwasha extract suppresses diabetes progression in db/db mice by preserving β-cell mass - Kaji, Megumi; Kaneko, Yukiko K.; Ihim, Stella Amarachi; Kanoh, Ran; Yamamoto, Moe; Yamaguchi, Momoka; Ishikawa, Tomohisa (Frontiers in Nutrition, 2024)
Nobiletin is a polymethoxyflavonoid abundant in citrus peels and has been reported to have various bioactive effects. We have previously reported that nobiletin inhibits endoplasmic reticulum stress-induced apoptosis in the pancreatic β-cell line INS-1 and that continuous subcutaneous administration of nobiletin suppresses the progression of diabetes by protecting β-cells in type 2 diabetic db/db mice. In the present study, we investigated effects of oral ingestion of Shiikuwasha extract rich in nobiletin on the pathogenesis of type 2 diabetes in db/db mice. Materials and methods: A Shiikuwasha extract was dissolved in MediDrop sucralose. Twenty-four mice were equally divided in three groups and fed with vehicle or low or high dose of Shiikuwasha extract for 4 weeks. Blood glucose levels, pancreatic β-cell mass, serum insulin levels, pancreatic insulin content, and other biomarkers were measured and compared between the groups. Results: The group that freely ingested the Shiikuwasha extract containing higher concentration of nobiletin (Shiikuwasha H) showed lower blood glucose levels. At the end of the experiment, the Shiikuwasha H group exhibited improved glucose tolerance, lower serum glycoalbumin levels, and an increase in β-cell area per pancreas compared with the control group. Body weight, food intake, and serum biomarkers related to liver function and lipid metabolism of the Shiikuwasha H group were not different from those of the control group, although water intake of the former was significantly decreased than that of the latter. Conclusion: Our results suggest that the oral ingestion of Shiikuwasha extract preserves pancreatic β-cell mass in diabetic mice, which might be attributed to ameliorating the progression of diabetes.